2020
DOI: 10.1186/s40545-020-00238-y
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase-4 inhibitors use in type II diabetic patients in a tertiary hospital

Abstract: Background: In Malaysia, for more than a decade, dipeptidyl peptidase-4 inhibitors (DPP-4i) are among the oral antidiabetic medications used as monotherapy or in combination to manage type II diabetes mellitus (T2DM). These medications are known for the efficacy in glycated haemoglobin (HbA1c) reduction and weight neutral effect with minimal hypoglycaemia occurrence. This study aimed to identify the outcomes of DPP-4i use in one of the largest tertiary public hospital in Southeast Asia. Methods: This is a retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The combination of dipeptidyl peptidase-4 (DPP-4) inhibitors such as vildagliptin (Figure 1A, VLG) and teneligliptin (Figure 1B, TNG) with the sodium-glucose cotrasportase-2 (SGLT-2) inhibitor, remogliflozin etabonate, (Figure 1C, RGE) has just been approved by the Food and Drug Administration for the treatment of diabetes mellitus type 2 [6,7]. DPP-4 inhibitors increase the secretion of insulin by inhibiting the enzyme DPP-4 responsible for degradation of incretins in the blood, thereby decreasing the blood glucose level by lowering the blood glucagon level, and improving pancreatic cell function [8,9]. DDP-4 inhibitors also lower HbA1c levels without causing hypoglycemia and weight gain [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of dipeptidyl peptidase-4 (DPP-4) inhibitors such as vildagliptin (Figure 1A, VLG) and teneligliptin (Figure 1B, TNG) with the sodium-glucose cotrasportase-2 (SGLT-2) inhibitor, remogliflozin etabonate, (Figure 1C, RGE) has just been approved by the Food and Drug Administration for the treatment of diabetes mellitus type 2 [6,7]. DPP-4 inhibitors increase the secretion of insulin by inhibiting the enzyme DPP-4 responsible for degradation of incretins in the blood, thereby decreasing the blood glucose level by lowering the blood glucagon level, and improving pancreatic cell function [8,9]. DDP-4 inhibitors also lower HbA1c levels without causing hypoglycemia and weight gain [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The simulation was then experimentally validated using recombinant DPP-IV in a calorimetric assay. The inhibition of DPP-IV has been proven as an effective and safe therapy for the treatment of type II diabetes mellitus since the last decade [33,34]. The results showed that the antidiabetic property of M. malabathricum was mainly contributed by quercetrin and partly attributed to other plant constituents.…”
Section: Anti-diabetic Activity Of Crude Extract and Fractionmentioning
confidence: 99%